Principal's Leadership Strategy in The Management of Rewards And Punishments to Improve Teacher Performance and Loyalty SMP BP Minnatul Huda - Asep Gopar Ismail; Trihadi Sulistyanto (ICON Publisher, 2026)
Quality education is closely associated with effective school leadership, particularly in managing teachers as essential human resources. One of the primary challenges faced by school principals is enhancing teacher performance and loyalty through appropriate leadership strategies. This study investigates the principal’s leadership strategy in managing reward and punishment systems to improve teacher performance and loyalty at SMP BP Minnatul Huda. It focuses on how these systems are planned, implemented, and evaluated, as well as their impact on teachers’ motivation, discipline, and organizational commitment. This research adopts a qualitative approach with a case study design. Data were collected through semi-structured, in-depth interviews involving key informants, including the Islamic boarding school leader, the foundation chairperson, and the school principal. Additional data were gathered from institutional documents and relevant literature. Informants were selected using purposive sampling, and source triangulation was applied to ensure the credibility and validity of the findings. The results reveal that the principal applies a transformational leadership approach supported by a structured, transparent, and participatory reward and punishment system. Rewards include financial incentives and non-financial recognition, while punishment is implemented constructively through a tiered system emphasizing professional development. These strategies significantly improve teacher motivation, discipline, performance, and loyalty. In conclusion, effective leadership combined with fair reward and constructive punishment practices plays a crucial role in enhancing teacher performance and sustaining educational quality.